Alternative ignition schemes in inertial confinement fusion - Tabak, M; Norreys, P; Tikhonchuk, V; Tanaka, K (Institute of Physics Publishing, 2014)
This paper presents a short overview of a series of review articles describing alternative approaches to ignition of fusion reactions in inertially confined plasmas. © 2014 IAEA, Vienna.